AMERICAN UNIVERSITY SEMINAR IN AFRICA (International Library of African Music, 1970)
A promising new development in American studies of African music was initiated recently when a six-week "Seminar in African Music and Art” organised by Manhattanville and Briarville Colleges, New York State, was held in West Africa in July-August 1969, led by Prof. Nicholas England, Hewitt Pantaleoni (whose article appears in this issue) and Mr. Seth Ladzekpo.
Keywords: African Music